If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -3(x + -1) = 15 Reorder the terms: 6x + -3(-1 + x) = 15 6x + (-1 * -3 + x * -3) = 15 6x + (3 + -3x) = 15 Reorder the terms: 3 + 6x + -3x = 15 Combine like terms: 6x + -3x = 3x 3 + 3x = 15 Solving 3 + 3x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3x = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 15 + -3 3x = 15 + -3 Combine like terms: 15 + -3 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 7y=2x-5 | | 5(2a+1)+16=3a | | 2(3x+2)+4(x+5)=4(x-2) | | 2(3x+2)+4(x+5)=4(x+-2) | | 5x-8=26 | | 2(3x+-2)+4(x+5)=4(x+-2) | | 6+7ln(2x-1)=62 | | (5y+6)(9y+7)=0 | | (3n-2)10=35 | | 3x/2+1/5=3x/5+1/2 | | 6x-1=4x+4 | | 9=3y+5 | | x^2+8x-330=0 | | -8r-7=-24 | | -36=2(x-4) | | 6x+12=30 | | 7x+2=3x+10 | | 20-5n=n+2 | | 4x^2*2x*12=0 | | 15-n=4 | | 4x^2*2x*12= | | 3(8-6n)=24 | | 2x+3=+7 | | 3n+1=n+3 | | 10+2n=0 | | 15-2n=19 | | 5n=200 | | 6n+11=5 | | 5x+29.75=3.25 | | 4n+1=3 | | 35x^2+9x-2=0 | | 10x+5=5x+10+5 |